2017
DOI: 10.3201/eid2304.161484
|View full text |Cite
|
Sign up to set email alerts
|

Variation inAedes aegyptiMosquito Competence for Zika Virus Transmission

Abstract: To test whether Zika virus has adapted for more efficient transmission by Aedes aegypti mosquitoes, leading to recent urban outbreaks, we fed mosquitoes from Brazil, the Dominican Republic, and the United States artificial blood meals containing 1 of 3 Zika virus strains (Senegal, Cambodia, Mexico) and monitored infection, dissemination, and virus in saliva. Contrary to our hypothesis, Cambodia and Mexica strains were less infectious than the Senegal strain. Only mosquitoes from the Dominican Republic transmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
186
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(203 citation statements)
references
References 37 publications
14
186
0
3
Order By: Relevance
“…On day 7 post-feeding, engorged mosquitos with similar blood meal sizes were analyzed for the presence of virus in the bodies to estimate viral infection rates. Consistent with previous findings (Roundy et al, 2017), WT virus showed an infection rate of 48% (Fig. 6).…”
Section: Resultssupporting
confidence: 92%
“…On day 7 post-feeding, engorged mosquitos with similar blood meal sizes were analyzed for the presence of virus in the bodies to estimate viral infection rates. Consistent with previous findings (Roundy et al, 2017), WT virus showed an infection rate of 48% (Fig. 6).…”
Section: Resultssupporting
confidence: 92%
“…However, recent in vivo and in vitro experimental work using a limited number of ZIKV strains demonstrated that the African lineage exhibits increased fitness/virulence in vertebrates as well as mosquito vectors compared to Asian lineage strains (Bowen et al, 2017; Weger-Lucarelli et al, 2016; Lazear et al, 2016; Roundy et al, 2017; Azar et al, 2017). Characterization of additional African strains in mosquito vectors, reservoir hosts and models for human infection, including early African isolates not available in reference collections are needed to fully explore the evolution of ZIKV, as well as to identify mutations potentially associated with differing phenotypes.…”
Section: Emergence and Spread Of Zikv Infectionmentioning
confidence: 99%
“…ZIKV transmission in the urban cycle mainly involves the anthropophilic Ae. aegypti mosquito (Marchette et al, 1969; Weger-Lucarelli et al, 2016; Roundy et al, 2017; Olson et al, 1981; Guerbois et al, 2016; Li et al, 2012; Boorman and Porterfield, 1956; Cornet et al, 1979b; Hall-Mendelin et al, 2016; Richard et al, 2016; Chouin-Carneiro et al, 2016), and to lesser degree the peridomestic Ae. albopictus (Azar et al, 2017; Grard et al, 2014; Wong et al, 2013), Ae.…”
Section: Mosquito Transmission and Control Measures (Nikos Vasilakis)mentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti and Ae. albopictus mosquitoes, which are associated with a risk of local transmission [15] as well other aedine species were heterogeneously and weakly competent for transmission [16][17][18][19][20][21][22][23][24][25]. Therefore, the potential role of other anthropophilic mosquitoes in the ZIKV outbreak raised a question which took time to be addressed [26].…”
mentioning
confidence: 99%